TINGKAT KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN TEMBAGA (Cu) DI SUNGAI BELAWAN KECAMATAN MEDAN SUNGGAL KOTA MEDAN (Level of Heavy Metal Content of Lead (Pb) and Copper (Cu) in the district of Medan Belawan River Sunggal Medan) - Rahmad Ritonga; Yunasfi Djayus; Maragunung Dalimunthe (AQUACOASTMARINE, 2014)
The river has an important role in the life of every living creature. In his role, the water will affect and are affected by the condition / other components. Water is often contaminated by inorganic components include a variety of dangerous heavy metals. Some heavy metals are widely used in a variety of daily needs and directly or indirectly, can pollute the environment and when it exceeds the limit specified hazardous to life. This study aims to analyze the content of heavy metal lead (Pb) and Copper (Cu) in the central part of Belawan River flow and water quality based Belawan River water quality standards. This research was conducted in March-April 2014 in the district of Medan Belawan River Sunggal Medan. The number of stations observed were 3 stations. Parameters measured were physical-chemical parameters of waters, concentrations of heavy metals lead and copper in the water column were analyzed using Atomic Abrsorption Spectrophotometry (AAS). Concentrations of heavy metals Lead (Pb) in water between 0 to 0.241 mg / l, and the concentration of heavy metals Copper (Cu) between 0 to 0.025 mg / l. This shows the heavy metal content of Pb and Cu in the central part of Belawan River flow has exceeded the standard.Keywords : Heavy metals Pb, Heavy metals Cu, Belawan River